2014
DOI: 10.1128/aem.02702-13
|View full text |Cite
|
Sign up to set email alerts
|

Osmoadaptation Strategy of the Most Halophilic Fungus, Wallemia ichthyophaga, Growing Optimally at Salinities above 15% NaCl

Abstract: Wallemia ichthyophaga is a fungus from the ancient basidiomycetous genus Wallemia (Wallemiales, Wallemiomycetes) that grows only at salinities between 10% (wt/vol) NaCl and saturated NaCl solution. This obligate halophily is unique among fungi. The main goal of this study was to determine the optimal salinity range for growth of the halophilic W. ichthyophaga and to unravel its osmoadaptation strategy. Our results showed that growth on solid growth media was extremely slow and resulted in small colonies. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 47 publications
1
96
0
Order By: Relevance
“…The uniqueness of the genus Wallemia is reflected by its phylogenetic position (Zalar et al 2005;Hibbett 2006;Matheny et al 2007;Padamsee et al 2012;Zajc et al 2013), however, also because of its extremophily. Representatives of the genus Wallemia can be defined as salt-tolerant halophiles, sugartolerant osmophiles, and xerophiles that tolerate low water activity in general (Wheeler et al 1988;Gock et al 2003;Zalar et al 2005;Kralj Kunčič et al 2010Zajc et al 2014). Xerotolerance, and even more so, xerophily, is relatively rarely observed in the fungal kingdom, specifically in Basidiomycota (de Hoog et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniqueness of the genus Wallemia is reflected by its phylogenetic position (Zalar et al 2005;Hibbett 2006;Matheny et al 2007;Padamsee et al 2012;Zajc et al 2013), however, also because of its extremophily. Representatives of the genus Wallemia can be defined as salt-tolerant halophiles, sugartolerant osmophiles, and xerophiles that tolerate low water activity in general (Wheeler et al 1988;Gock et al 2003;Zalar et al 2005;Kralj Kunčič et al 2010Zajc et al 2014). Xerotolerance, and even more so, xerophily, is relatively rarely observed in the fungal kingdom, specifically in Basidiomycota (de Hoog et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As W. ichthyophaga requires at least 1.5 M NaCl in its culture medium for growth, but thrives also in saturated NaCl solutions (Zalar et al 2005;Kralj Kunčič et al 2010), it was considered as the most halophilic fungus known to date. In recent years, it has become an important model organism for the study of haloadaptation in eukaryotes (Kralj Kunčič et al 2010;Lenassi et al 2011;Konte and Plemenitaš 2013;Zajc et al 2013Zajc et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that these isolates required a certain level of NaCl in the culture medium, because of their origin from salt-affected soils. Similarly, diverse findings reported that some microorganisms prefer or require a high salt (NaCl) medium to grow (Kralj Kuncic et al 2010;Zajc et al 2014). For example, Wallemia ichthyophaga is a fungus that grows only on solid or liquid medium supplemented with NaCl at concentrations between 15 and 20 % (wt/vol) .…”
Section: Discussionmentioning
confidence: 99%
“…Ceramides may also interact with ergosterol as structural molecules in the membrane, and two genes for ceramide metabolism were upregulated. Differential expression of a number of genes involved in cell wall structure and remodelling points to a role for cell wall rigidity/flexibility during osmotic stress, as noted in the extremely xerophilic yeast, Zygosaccharomyces rouxii (Přibylová et al, 2007), and the halophile W. ichthyophaga and related species (Kralj Kunčič et al, 2013;Zajc et al, 2014). Four mannosyltransferases, two of which appear to be a duplication of PMT1, were upregulated -these have predicted roles in O-glycosylation, which contributes to cell wall rigidity, as well as anchoring membrane proteins to the lipid bilayer of the cell membrane via glycosylphosphatidylinositol (Orlean, 1990;Bourdineaud et al, 1998;Sutterlin et al, 1998).…”
Section: Membrane Fatty Acid Saturation Is Increased At Low Water Actmentioning
confidence: 98%